Treatment decision making on insulin for type 2 diabetes: An analysis of activity and account / Sharifah Ayeshah Syed Mohd Noori - Sharifah Ayeshah, Syed Mohd Noori (2019)
Low adoption of insulin therapy for type 2 diabetes leaves many patients at risk of complications. A patient decision aid (PDA) was developed to facilitate informed and shared decision making (SDM) in consultations about starting insulin (DMIT Group, 2012). However, there is limited interactional data about PDA use and treatment decision making in Malaysia. This study applies Theme-oriented Discourse Analysis (Roberts & Sarangi; Sarangi, 2010a, 2010b) to study treatment decision making about insulin as activity and account, by analyzing two types of discursive data: doctor-patient consultations and research interviews with doctors and patients. Data were transcribed using Jefferson notation for the consultations and standard orthography for the interviews. Activity Analysis was applied to the consultations, beginning with mapping of whole consultations and followed by closer analysis of talk, to examine doctors’ and patients’ practices in using the PDA and negotiating treatment decisions. Accounts Analysis was then used to analyse the rhetorical practices of doctors and patients in constructing accounts of treatment decision making in the interviews. Activity Analysis of the consultations showed that the main consultation phases were Assessment and Treatment, with Assessment serving the rhetorical function of supporting doctors’ recommendations. Consultations were mostly doctor-driven, becoming longer and more iterative when patients had not read the PDA or resisted insulin. Doctors asked questions about the PDA to determine if patients were “informed” and used the PDA to provide information about insulin only if patients had not read it. Otherwise, doctors initiated talk on treatment by eliciting patient perspectives. Although they elicited patient participation, doctors’ questions also constrained patient responses and their selective PDA use had implications for SDM. Treatment negotiation was largely driven by doctors’ questions while patient responses conveyed resistance directly or indirectly. Negotiations ended on shared footing with either the patient accepting insulin or the doctor accepting the patient’s preferred treatment. In displays of professional or personal responsibility, doctors and patients deployed different meanings of control in their accounts: the biomedical measure of sugar control, controlling the disease, controlling the self, controlling the patient and controlling the decision. Doctors and patients used various discursive and rhetorical devices, including character work, event work and contrast, to construct their accounts. Doctors’ accounts foregrounded their attempts to gain the patient’s acceptance of insulin, while aligning their practices with patient-centred ideals. While doctors and patients invoked the patient’s ultimate control over his health, patients who accepted insulin conveyed a loss of control. Conversely, those who refused insulin emphasised their control over their diet and blood sugar, which legitimised their treatment choice. Findings show that doctors’ practices while using the PDA can facilitate or constrain patient knowledge and choice in decision making. However, pursuing patient acceptance may not contradict SDM principles, as insulin is the medically recommended treatment in this context and all the decisions eventually ended on shared footing. Because patients may have negative perspectives towards insulin, including viewing it as a loss of control, insight into interactional practices can aid doctors in managing potential conflicts during treatment decision making.